The The Influence of Service Quality and Facilities on Customer Satisfaction at Tambika Restaurant - Rezki, Rendi; Efi, Agusti (Jurnal Penelitian Pariwisata, 2025)
This study aims to analyze the effect of service quality and facilities on customer satisfaction at Tambika Restaurant. The approach used is a quantitative method. The population of the study was Tambika customers who had eaten at the restaurant. The sample used was 100 people. The results of the study showed that there was an effect of service quality and facilities on customer satisfaction at Tambika Restaurant, showing an Fhit result of 48.575 with a significant value = 0.000. Because in the significant column 0.000 <0.05, there is a significant influence between the independent variables, namely service quality and facilities, with the dependent variable, namely customer satisfaction at the restaurant. The results of the empirical analysis, service quality has a significant positive effect on customer satisfaction, it is known that t count = 3.207 with sig = 0.002 <0.05. The facility variable also shows a significant influence on restaurant customer satisfaction (Y). The results of multiple regression analysis show that t count = 3.129 with sig = 0.002 < 0.05, which indicates that facilities have a positive and significant effect on customer satisfaction at Tambika Restaurant. Considering that service quality has a significant influence on customer satisfaction, Tambika Restaurant is advised to continue to improve employee service competency and attitudes, such as friendliness, speed of service, and ability to respond to customer complaints. Keywords: Quality, Service, Facilities, Satisfaction, Consumers